Barriers and drivers for sustainable public transportation in Indian context - R G.; Pathak D.V.; Pratap S.; Lakshay (My University, 2025)
Rising negative externalities, including greenhouse gas emissions, climate change, and environmental pollution, shows the need for sustainable and environmentally friendly modes of transportation. Adopting zero-emission, environmentally friendly electric buses in public transportation systems can be an effective solution for both developing and developed countries, including India. While the Indian government is making numerous efforts to promote electric buses in commercial and public transportation systems, it faces several formidable obstacles. This research objective is to analyze and evaluate the primary factors influencing the adoption and usage of electric buses in the Indian public transportation system, within the limited available resources. A survey questionnaire is prepared with several perceptual subjects for the key perceived barriers. An empirical analysis using Structural Equation Modeling (SEM) is then performed to identify the critical barriers. The result of this study demonstrates that the infrastructural barriers substantially impact the adoption and utilization of electric buses. Further, the study provides critical insights and managerial implications for decision-makers. © 2023 The Author(s)